From Compassion to the Capitalization of Resources. Spanish Confessional Health Centers within the scope of Spanish Health Cooperation with Equatorial Guinea - Jones Sánchez, Alvar (Revista de Antropología Social, 2016)
This article presents the main stages of Spanish health cooperation in Equatorial Guinea, focusing on the factors that have established the Spanish congregations’ health centers as the market’s most competitive therapeutic alternatives. Congregations, a key element in the colonization process, have been mobilized again in order to match the neocolonial whims of the Spanish State. Combining a socio-historical and an ethnographic perspective, this article questions the quality of the activity of confessional health centers, not so much from the technical point of view as from the perspective of the implications that the construction of health archipelagos may have in the consolidation of the incipient health care system. The tensions between missionary goals, markedly assistanceoriented, and the current approaches to development, show the ambiguities of Spanish cooperation in Equatorial Guinea. Aid, presented as a moral imperative, has mobilized flexible and sometimes contradictory meanings which must be unraveled. A reflection on revealed goals and unformulated aims governing neo-colonial relations will enable us to understand the distance between the aims and the achievement of results.
Keywords: Equatorial Guinea; Spanish development aid; Spanish religious congregations; Equatorial Guinea health system.